Isolation of Luminescent Bacteria on Loligo duvauceli and Euprymna berryi squid - Abdul Kodir Jaelani; Delianis Pringgenies (Jurnal Moluska Indonesia, 2019)
Bioluminescence is known to be found in squids. Bioluminescence occurs as a result of reactions from within the body (intrinsic bioluminescence) or by luminescent bacteria that are outside the body (extrinsic bioluminescence). This study aims to examine the results of the isolation of luminescent bacteria found in the light organs of Loligo duvauceli and Euprymna berryi squid. Squid sampling was carried out in the waters of Awur Bay, Jepara. Meanwhile, bacterial isolation and analysis were carried out in the Laboratory of Aquatic Animal Health Management (MKHA) of the Central for Brackish Water Cultivation Development (BBPBAP) Jepara. The research method used in this research is descriptive method with the sampling technique using purposive sampling technique. The results of the research on Loligo duvauceli squid obtained 2 isolates of luminescent bacteria, 1 isolate from N.A. and 1 isolate from TCBSA media. Whereas in Euprymna berryi squid there were also 2 isolates, 1 isolate from N.A. and 1 isolate from TCBSA media. The glow produced by luminescent bacteria is bluish green. In general, the luminescent bacteria isolated from the Loligo duvauceli squid was stronger than the light rays of the bacteria isolated from the Euprymna berryi squid. The total number of luminescent bacterial colonies found in the light organ of Loligo duvauceli squid was 15.47.108 CFU / mL. While the total number of luminescent bacterial colonies in the light organ of the squid Euprymna berryi was 15.1.107 CFU / mL.